STRUKTUR KOMUNITAS GULMA PADA KEBUN NANAS (Ananas comosus L.) DI DESA PENDOPO KECAMATAN TALANG UBI KABUPATEN PENUKAL PALI SUMATERA SELATAN - Inka Dahlianah (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2015)
Research on the structure of weed community in the gardens pineapple (Ananas comosus L.) was conducted in January to February 2015 in the Village Hall District of Talang Ubi Penukal Abab Lematang Ilir Regency (PALI) South Sumaetra Province. The research aims to determine the structure and composition of existing weeds. Research using squares method with the unit area sample plot (Plot Analisys Method). Data analysis included density, relative density, frequency, relative frequency and importance value index. Results of the study found 10 species of weeds are Amaranthus spinosus (spinach with thorns), Ageratum conyzoides (babandotan), Cyperus rotundus (nutgrass), Phyllanthus niruri (meniran), Sauropus androgynus (katuk), Acalypha indica (kucingan), Mimosa pudica (daughter of shame ), Elusine indica (grassbones), Nephrolepis bisserata (nephrolepis) and Davallia denticulata (spikes closed). Nephrolepis bisserata a dominant weed was found, with the IVI 31.6%.Â Key words:Â  structure of weed, community, Ananas comosus L